Sharing stakeholder knowledge across water management boundaries and interfaces: experiences from Australian and New Zealand 'HELP' basins. Issue 1 (2nd January 2016) - Camkin, Jeff
Abstract: As water management issues have grown and become more connected, the need to engage civil society and incorporate a wider range of community knowledge in decision-making is increasingly recognised. This paper discusses experiences of three river basins that are part of the UNESCO-IHP Hydrology for the Environment, Life and Policy programme. In each, water management issues cross different kinds of 'boundaries'. At the Ord River, north-western Australia, investment in irrigation expansion and social infrastructure is driving the need for more comprehensive water planning and management incorporating a new set of economic, social and ecological values, new knowledge sources, and more collaboration with the neighbouring jurisdiction. In the lower Burdekin, north-eastern Australia, sugar cane irrigators need to reduce their impact on local groundwater, wetlands and adjacent Great Barrier Reef. And at the Motueka River, on New Zealand's South Island, an 11-year Integrated Catchment Management programme sought solutions to the impacts of upstream land use on downstream water quality. While none of the basins physically crosses an international or national boundary, they can all be considered transboundary waters. These examples show that many of the challenges experienced in relation to international transboundary resources are replicated at other scales and in other ways: across internal borders, through institutional confines, across environmental interfaces, between economic sectors and around a range of social norms. Understanding the various boundaries can help identify a more comprehensive and inclusive suite of stakeholders, enabling their interests and knowledge to be incorporated into decision-making. Sharing knowledge across these boundaries is critical to developing the mutual understanding necessary to support better water management and more equitable benefit-sharing from available water resources.